Therapeutic Affordances of Social Media: Emergent Themes From a Global Online Survey of People With Chronic Pain - Merolli, Mark; Gray, Kathleen; Martin-Sanchez, Fernando (JMIR Publications, 2014)
BackgroundResearch continues to present tenuous suggestions that social media is well suited to enhance management of chronic disease and improve health outcomes. Various studies have presented qualitative reports of health outcomes from social media use and have examined discourse and communication themes occurring through different social media. However, there is an absence of published studies examining and unpacking the underlying therapeutic mechanisms driving social media's effects. ObjectiveThis paper presents a qualitative analysis thoroughly describing what social media therapeutically affords people living with chronic pain who are self-managing their condition. From this therapeutic affordance perspective, we aim to formulate a preliminary conceptual model aimed at better understanding "how" social media can influence patient outcomes. MethodsIn total, 218 people with chronic pain (PWCP) completed an online survey, investigating patient-reported outcomes (PROs) from social media use. Supplementary to quantitative data collected, participants were also given the opportunity to provide further open commentary regarding their use of social media as part of chronic pain management; 68/218 unique users (31.2%) chose to provide these free-text responses. Through thematic content analysis, 117 free-text responses regarding 10 types of social media were coded. Quotes were extracted and tabulated based on therapeutic affordances that we had previously identified. Inductive analysis was then performed to code defining language and emergent themes central to describing each affordance. Three investigators examined the responses, developed the coding scheme, and applied the coding to the data. ResultsWe extracted 155 quotes from 117 free-text responses. The largest source of quotes came from social network site users (78/155, 50.3%). Analysis of component language used to describe the aforementioned affordances and emergent themes resulted in a final revision and renaming of therapeutic affordances: "exploration" (52/155, 33.5% of quotes), "connection" (50/155, 32.3% of quotes), "narration" (33/155, 21.3% of quotes), "adaptation" (13/155, 8.4% of quotes), and "self-presentation" (7/155, 4.5% of quotes). Of the most described affordances, "exploration" was based on a propensity for participants to explain their social media use for information seeking purposes. "Connection" placed greater emphasis on interaction, highlighting themes of "exchanging information" and "mitigating isolation". Responses regarding "narration" highlighted the value of shared experiences and the emotionally cathartic role this plays. ConclusionsMuch of the efficacy of social media may be explicable via a closer examination of therapeutic affordances. Particular areas that warrant attention include social media's ability to filter and guide people to useful information, connect individuals, and share experiences. Further research into a variety of chronic conditions is warranted. Coupled with the results of the present study, a greater theoretical basis detailing how social media may foster health outcomes may lead to an improved evidence base for conducting research and may inform recommendations for social media use in chronic disease management.